Masalah Sosial dalam Novel Kado Terbaik Karya J.S. Khairen Sebagai Alternatif Bahan Ajar di Sekolah Menengah Atas - Amelia, Safira; Widayati, Sri; Ratnaningsih, Dewi (Edukasi Lingua Sastra, 2025)
The problem in this study is the social problem in the novel Kado Terbaik by J.S. Khairen as an alternative teaching material in high school. The purpose of this study is to describe the social problem in the novel Kado Terbaik by J.S. Khairen and determine the feasibility of the novel. as an alternative teaching material in high schools. The method used in this study is a descriptive method with a qualitative approach. The results of the study indicate that there are social problems in the novel Kado Terbaik by J.S. Khairen, namely 1) poverty, 2) crime, 3) family disorganization, 4) problems of the younger generation in modern society, 5) violations of community norms, 6) and environmental problems. The novel Kado Terbaik by J.S. Khairen is worthy of being used as an alternative teaching material in high schools because the criteria for linguistic, psychological, and cultural background aspects of students have been met.